Immigrants' occupational mobility—Down and back up again - Aslan Zorlu (IZA World of Labor, 2016)
Evidence suggests that immigrants face an initial decline in their occupational status when they enter the host country labor market but that their position improves as they acquire more country-specific human, cultural, and occupational capital. High-skilled immigrants from countries that are economically, linguistically, and culturally different from the host country experience the greatest decline and the steepest subsequent increase in their occupational status. In the context of sharp international competition to attract high-skilled immigrants, this adjustment pattern is contradictory and discourages potential high-skilled migrants.
Keywords: J6; J61; J24; 330; occupation; immigration; skill transferability